BRAF(V600E) inhibition stimulates AMP-activated protein kinase-mediated autophagy in colorectal cancer cells - Sueda, Toshinori (Sci Rep, 2016)
Although BRAF(V600E) mutation is associated with adverse clinical outcomes in patients with colorectal cancer (CRC), response and resistance mechanisms for therapeutic BRAF(V600E) inhibitors remains poorly understood. In the present study, we demonstrate that selective BRAF(V600E) inhibition activates AMP-activated protein kinase (AMPK), which induces autophagy as a mechanism of therapeutic resistance in human cancers. The present data show AMPK-dependent cytoprotective roles of autophagy under conditions of therapeutic BRAF(V600E) inhibition, and AMPK was negatively correlated with BRAF(V600E)-dependent activation of MEK-ERK-RSK signaling and positively correlated with unc-51-like kinase 1 (ULK1), a key initiator of autophagy. Furthermore, selective BRAF(V600E) inhibition and concomitant suppression of autophagy led to the induction of apoptosis. Taken together, present experiments indicate that AMPK plays a role in the survival of BRAF(V600E) CRC cells by selective inhibition and suggest that the control of autophagy contributes to overcome the chemoresistance of BRAF(V600E) CRC cells.